Implementasi Permainan Pickleball Sebagai Media Pembelajaran Pendidikan Jasmani dalam Meningkatkan Keterampilan Motorik Kasar Siswa Sekolah Dasar - Nofulan Adyani; Anung Priambodo; Sapto Wibowo (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aimed to analyze the effect of implementing Pickleball on improving students’ gross motor skills in physical education. A quantitative approach with a quasi-experimental one-group pretest–posttest design was used. The research sample consisted of 45 fourth-grade students from SDN Suko 2 Sidoarjo, selected through purposive sampling. The instrument used was a gross motor skill test covering balance, coordination, speed, and large muscle strength. Data were analyzed using descriptive statistics, prerequisite tests, and a Paired Sample t-Test at a 0.05 significance level. The results showed a significant improvement in gross motor skills, with mean scores increasing from 68.24 to 84.67 (t = -11.258; p = 0.000). It was concluded that Pickleball effectively enhances gross motor skills and serves as an engaging, adaptable learning medium in the Merdeka Curriculum. Keywords: Pickleball, physical education, gross motor skills, elementary school students